2011
DOI: 10.2139/ssrn.1979694
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Great Recession on School District Finances: Evidence from New York

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 1 publication
2
20
1
Order By: Relevance
“…In an analysis presented to the Federal Reserve Bank of New York, Chakrabarti and Setren (2011) examined the effect of the Great Recession on New York State public schools. In contrast to the finding by Freelon et al (2012), Chakrabarti and Setren found that more affluent schools were affected by the recession to a greater extent than their less affluent peer districts.…”
Section: Great Recession's Influence On School District Budgetsmentioning
confidence: 99%
See 3 more Smart Citations
“…In an analysis presented to the Federal Reserve Bank of New York, Chakrabarti and Setren (2011) examined the effect of the Great Recession on New York State public schools. In contrast to the finding by Freelon et al (2012), Chakrabarti and Setren found that more affluent schools were affected by the recession to a greater extent than their less affluent peer districts.…”
Section: Great Recession's Influence On School District Budgetsmentioning
confidence: 99%
“…Though scholars have examined the macro effects of the recession on school districts (Chakrabarti & Setren, 2011;Dupor & Mehkari, 2015;Leachman & Mai, 2014), few scholars in gifted education have examined the numerous specifics of how those effects manifested in district-level funding choices. The purpose of this study was to examine the effect of the financial crisis on the budget for gifted education in Texas public school districts.…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations
“…However, responses to the drop in revenues vary by state and school district. Using school district-level data, Chakrabarti and Setren (2011) found that although instructional expenditure was maintained since 2004-05, other categories such as transportation, student activities -including athletics -and utilities suffered.…”
Section: Introductionmentioning
confidence: 99%